RESEARCHING THE -ING FORMS IN ENGLISH - I Gusti Nyoman Putra Kamayana (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACT  The use of -ing form is enormously extensive in English and possibly poses some conceptualgrammatical difficulties for English teachers and learners . On the one hand, -ing morpheme is attached to a verbal base resulting in a verbal form and function . such form and function canbe assumed to be the default case . on the other hand, -ing morpheme can be also attached to a verbal base, but bring about adjectival and nominal functions. In relation to such usages of -ing, Nida (1949) suggests that -ing should simply be treated as a single morpheme with various usages. As a matter of fact, despite being used as a noun or adjective , -ing forms still keeptheir verbal force. The case of -ing forms uncovers the point where word-class indeterminacyexists and therefore they are prevailingly regarded as trans-categorial , a sort of ‘hybrid category’ and ‘seem to be core members of more than one category simultaneously’(Alexiadou 2013 : Malouf 1996) . The paper has two objectives: firstly, to elaborate the idiosyncrasies of -ing forms which are certainly valuable for English teaching and learning andsecondly, to examine the distributions of -ing form in a small English Narrative corpus byemploying a quantitative analysis.  Key words : -ING form, nominal gerund, present particip le, verbal gerund  ABSTRAK Penggunaan bentuk -ing sangat luas dalam bahasa Inggris dan mungkin menimbulkan beberapa kesulitan gramatikal konseptual untuk guru bahasa Inggris dan peserta didik. Disatu sisi, morfem melekat pada basis verbal sehingga menghasilkan bentuk dan fungsi verbal. Bentuk dan fungsi semacam itu bisa diasumsikan sebagai kasus yang sering terjadi. Di sisilain, morfem juga bisa dikaitkan dengan basis verbal, namun menghasilkan fungsi adjectival dan nominal. Sehubungan dengan penggunaan-penggunaan semacam itu, Nida (1949)mengemukakan bahwa - seharusnya hanya diperlakukan satu morfem tunggal dengan berbagai penggunaan. Sebenarnya, meski digunakan sebagai kata benda atau kata sifat,bentuknya tetap mempertahankan kekuatan verbal mereka. Kasus bentuk-bentuk mengungkaptitik di mana ketidakpastian kelas kata ada dan karena itu mereka dianggap sebagai trans-categorial, semacam 'kategori hibrida' dan 'tampaknya merupakan anggota inti dari lebih darisatu kategori secara bersamaan' (Alexiadou 2013 : Malouf 1996). Makalah ini memiliki dua tujuan: pertama, untuk menguraikan keistimewaan bentuk-bentuk yang tentu saja sangatberharga untuk pengajaran dan pembelajaran bahasa Inggris dan kedua, untuk memeriksadistribusi bentuk       -ing dalam sebuah Narasi bahasa Inggris kecil dengan menggunakan analisis kuantitatif. Kata kunci: bentuk -ing, nominal, verbal